Stakeholder and Stockholder Viewpoints of Corporate Ethics: A Comparison among Senior Business Students, MBA Students and Managers - Russell Ryan Spears (Sekolah Tinggi Manajemen IPMI, 2023)
To contribute to the ethics literature, this study collects data from senior business students, MBA students, and managers, to assess whether there are within and between group differences in perceived stakeholder and stockholder views, controlling for gender, age and work experience. The results indicate that, for both seniors and MBA students, their perception of the stakeholder view is significantly greater than that for the stockholder view. Conversely, managers identify more closely with the stockholder view, The results also indicate that managers have a significantly lower (higher) perception of the stakeholder (stockholder) view than either of the student groups. Senior business students have a higher (lower) perception of the stakeholder (stockholder) view than MBA students.